A Voronovskaja-type formula for the \(q\)-Meyer-König and Zeller operators - Trif, Tiberiu (Rev. Anal. Numér. Théor. Approx., 2011)
A Voronovskaja-type formula for the \(q\)-Meyer-König and Zeller operators is presented.